Genome Analyses of the Microalga Picochlorum Provide Insights into the Evolution of Thermotolerance in the Green Lineage. (3rd August 2018) - Krasovec, Marc; Vancaester, Emmelien; Rombauts, Stephane; Bucchini, François; Yau, Sheree; Hemon, Claire; Lebredonchel, Hugo; Grimsley, Nigel; Moreau, Hervé; Sanchez-Brosseau, Sophie; Vandepoele, Klaas; Piganeau, Gwenael
Abstract: While the molecular events involved in cell responses to heat stress have been extensively studied, our understanding of the genetic basis of basal thermotolerance, and particularly its evolution within the green lineage, remains limited. Here, we present the 13.3-Mb haploid genome and transcriptomes of a halotolerant and thermotolerant unicellular green alga, Picochlorum costavermella (Trebouxiophyceae) to investigate the evolution of the genomic basis of thermotolerance. Differential gene expression at high and standard temperatures revealed that more of the gene families containing up-regulated genes at high temperature were recently evolved, and less originated at the ancestor of green plants. Inversely, there was an excess of ancient gene families containing transcriptionally repressed genes. Interestingly, there is a striking overlap between the thermotolerance and halotolerance transcriptional rewiring, as more than one-third of the gene families up-regulated at 35 °C were also up-regulated under variable salt concentrations in Picochlorum SE3 . Moreover, phylogenetic analysis of the 9, 304 protein coding genes revealed 26 genes of horizontally transferred origin in P. costavermella, of which five were differentially expressed at higher temperature. Altogether, these results provide new insights about how the genomic basis of adaptation to halo- and thermotolerance evolved in the green lineage.